Paul of Aleppo's Journal : Syria, Constantinople, Moldavia, Wallachia and the Cossacks' Lands - Feodorov, Ioana, (Arabic Christianity ;, 2024)
Paul of Aleppo, an archdeacon of the Church of Antioch, journeyed with his father Patriarch Makarios III ibn al-Za'im to Constantinople, Moldavia, Wallachia and the Cossack's lands in 1652-1654, before heading for Moscow. This book presents his travel notes, preceded by his record of the patriarchs of the Church of Antioch and the story of his father's office as a bishop and election to the patriarchal seat. The author gives detailed information on the contemporary events in Ottoman Syria and provides rich and diverse information on the history, culture, and religious life of all the lands he travelled across.